JUNIOR SECONDARY SCHOOL STUDENTS’ EVALUATION OF THEIR BASIC SCIENCE TEACHERS’ INSTRUCTIONAL EFFECTIVENESS IN AWKA SOUTH (UNIZIK Journal of STM Education, 2021)
The study investigated junior secondary school students’ evaluation of their Basic Science teachers’ instructional effectiveness. Three research questions guided the study. The study made use of the survey research design. The research was done in Awka South Local Government Area of Anambra State. The sample of the study constituted of 300 J.S.S. 2 students. The instrument titled Teachers Instructional Effectiveness Evaluation Questionnaire (TIEEQ), adapted from the NUC rubric for students’ evaluation of teachers in the tertiary institutions was used for data collection. A reliability coefficient of 0.85 using Cronbach alpha was obtained for the instrument. The Mean was used in answering the research questions. The major findings from the study showed that students were in agreement that their Basic Science teachers were effective in the areas of lesson organization and planning, teacher-student interaction and the use of instructional materials which were covered by the study. It was recommended among other things that school authorities should use students’ evaluation of teaching for evaluating teachers’ teaching effectiveness.
Keywords: Basic Science; teachers‘ effectiveness; students‘ evaluation